Impact of Over-the-Counter Restrictions on Antibiotic Consumption in Brazil and Mexico - Santa-Ana-Tellez, Yared (Public Library of Science, 2013)
BACKGROUND: In Latin American countries over-the-counter (OTC) dispensing of antibiotics is common. In 2010, both Mexico and Brazil implemented policies to enforce existing laws of restricting consumption of antibiotics only to patients presenting a prescription. The objective of the present study is therefore to evaluate the impact of OTC restrictions (2010) on antibiotics consumption in Brazil and Mexico. METHODS AND FINDINGS: Retail quarterly sales data in kilograms of oral and injectable antibiotics between January 2007 and June 2012 for Brazil and Mexico were obtained from IMS Health. The unit of analysis for antibiotics consumption was the defined daily dose per 1,000 inhabitants per day (DDD/TID) according to the WHO ATC classification system. Interrupted time series analysis was conducted using antihypertensives as reference group to account for changes occurring independently of the OTC restrictions directed at antibiotics. To reduce the effect of (a) seasonality and (b) autocorrelation, dummy variables and Prais-Winsten regression were used respectively. Between 2007 and 2012 total antibiotic usage increased in Brazil (from 5.7 to 8.5 DDD/TID, +49.3%) and decreased in Mexico (10.5 to 7.5 DDD/TID, −29.2%). Interrupted time series analysis showed a change in level of consumption of −1.35 DDD/TID (p<0.01) for Brazil and −1.17 DDD/TID (p<0.00) for Mexico. In Brazil the penicillins, sulfonamides and macrolides consumption had a decrease in level after the intervention of 0.64 DDD/TID (p = 0.02), 0.41 (p = 0.02) and 0.47 (p = 0.01) respectively. While in Mexico it was found that only penicillins and sulfonamides had significant changes in level of −0.86 DDD/TID (p<0.00) and −0.17 DDD/TID (p = 0.07). CONCLUSIONS: Despite different overall usage patterns of antibiotics in Brazil and Mexico, the effect of the OTC restrictions on antibiotics usage was similar. In Brazil the trend of increased usage of antibiotics was tempered after the OTC restrictions; in Mexico the trend of decreased usage was boosted.